MALARIA NO MUNICIPIO DE HUMAITA, ESTADO DO AMAZONAS. VIII. COMPORTAMENTO DAS TAXAS DE HEMOGLOBINA A2 EM HABITANTES DA REGIAO E EM DOENTES - Matsubara, L. S.; De Abreu Machado, P. E.; Meira, D. A. (My University, 1981)
Haemoglobin A2 levels were measured in 25 patients with acute malaria and in 55 non-infected individuals (11 Indians, 22 inhabitants from the Rio Madeira shore and 12 dwellers of one of the town quarters named Olaria), all living at Humaita in the State of Amazonas, Brazil. Haemoglobin A2 levels did not differ statistically between the malaria patients (x̄ = 3.06% ± 0.62%) and two of the non-infected groups (Indians: x̄ = 3.13% ± 0.67% and Madeira River shore inhabitants: x̄ = 2.79% ± 0.59%. The Olaria town dwellers showed a haemoglobin A2 level significantly lower than that of the three others groups (x̄ = 2.18% ± 0.44%). This finding may be related both to their poorer living conditions and higher incidence of helminthiasis leading to iron deficiency, with a consequent decrease in the hemoglobin A2 synthesis.
Malaria at Humaita County, Amazonas State, Brasil. VIII. Haemoglobulin A2 levels in healthy inhabitants and in patients